Hepatitis G virus infection among Iraqi patients on maintenance hemodialysis - Al-Karkhy, Mohammad A.; Abdullah, Shatha F.; Allawi, Ali A. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Patients on maintenance hemodialysis are at increased risk of infection with parentally transmitted viral agents. In recent years a high prevalence of hepatitis G virus infection among end stage renal diseases and chronic hemodialysis patients has been well documented.Objectives: To assess the percentage and risk factors of HGV in hemodialysis patients, and to evaluate the clinical consequences of HGV in this population.Patients and methods: Fifty (50) patients with chronic renal failure who underwent maintenance hemodialysis. Patients were currently attending hemodialysis department of Baghdad teaching hospital during the period of October 2011 to January 2012, compared to forty one (41) healthy blood donors who underwent a full blood screening tests collected from blood bank. Aged matched as a control group. Anti-Hepatitis G antibodies (IgM and IgG) were detected using enzyme linked immunosorbant assay and HGV-RNA was determined by RT-PCR.Results: Hepatitis G virus -IgM and HGV-IgG were detected in 26 patients (52%) and in 36 patients (72%) respectively. HGV-RNA was detected in 16 patients (32%). Furthermore, nine (18%) patients revealed HGV-RNA bands and gave a positive HGV-IgM. Hepatitis G virus was significantly associated with the history and numbers of blood pints intake among hemodialysis patients, while there were no association with the hemodialysis duration, history of renal transplant nor with raised liver enzymes.Conclusions: Our results showed that hemodialysis patients carry the risk for HGV infection as a major possibility of parenteral transmission, especially by transfusion of blood and blood components. Decisions to screen blood supplies for a transfusion-transmitted infection agent should be based on sufficient benefits for recipients.